Antimicrobial activity and mechanism of action of oregano essential oil against Morganella psychrotolerans and potential application in tuna. (1st August 2022) - Wang, Di; Li, Chunsheng; Pan, Chuang; Wang, Yueqi; Xiang, Huan; Feng, Yang; Yang, Xianqing; Chen, Shengjun; Zhao, Yongqiang; Wu, Yanyan; Li, Laihao; Kawai, Yuji; et al.
Abstract: Morganella psychrotolerans is a psychrotolerant histamine producer capable of accumulating large amounts of histamine at low temperatures. Oregano essential oil (OEO) is a natural antimicrobial agent used widely in the food industry, however, its antimicrobial effectiveness against M. psychrotolerans has not been studied. In this study, the inhibitory activity of OEO against M. psychrotolerans, causing damage to the membrane structure of the cell with 0.025% (v/v) minimum inhibitory concentration (MIC) has been revealed. Metabolomics analysis revealed changes of 161 significant metabolites in ESI + and ESI – modes, which involved in carbohydrates metabolism, amino acid metabolism, metabolism of cofactors and vitamins, nucleotides metabolism, lipids metabolism, and energy metabolism. Furthermore, challenge tests revealed the OEO exhibited a significant inhibitory effect on M. psychrotolerans in tuna. These results provided new insights into the inhibition action of OEO on M. psychrotolerans and suggested that OEO had the potential to control M. psychrotolerans in the seafood industry. Graphical abstract: Image 1 Highlights: OEO showed good antibacterial activity against M. psychrotolerans. Cell membrane structure of M. psychrotolerans was destroyed after OEO treatment. Antimicrobial mechanism of OEO was revealed from the metabolism level. Metabolic pathways were significantly disordered after OEO treatment. OEO can inhibit M. psychrotolerans growth in tuna.